Knowledge and Practice towards Self -Medication among University of Kerbala Students: Self-Medication - abid, eman mohammed (Karbala Journal of Medicine, 2024)
Abstract Background: In general, the use of medicines divided into prescription-only medicines and over-the-counter drugs. The former requires a medical prescription; the latter are available for self-medication of common minor and easily treated illness. However, in the developing countries, prescription-only medicines can easily be purchased without a prescription, resulting in potential misuse and unnecessary risk for individuals. Objectives: Evaluate the knowledge and practice among University of Kerbala students of about self-medication. Subjects and Methods: A cross-sectional study has been implemented in the University of Kerbala among seven colleges included both medical and non-medical colleges selected by a multistage cluster sampling technique while the students were chosen by simple random sampling technique. Data were collected through questionnaire papers in Arabic during April & May 2019. Results: The selected sample have a low mean knowledge score (4.83 ± 2.16) about the proper use of medications and drug safety. Especially regarding appropriate antibiotic use, with a correctness rate of 25.4. Two thirds of the sample (62.1%) practiced self-medication with no significant difference between medical and non‑medical students. Conclusion: This study showed that selected sample from the University of Kerbala has low level of knowledge about the proper use of medications and drug safety. About two-thirds of selected sample practiced self-medication for both over the counter and prescription-only medications. There is an irrational use of antibiotics, which needs attention by health institutions in Iraq.